Адміністративний примус як метод реалізації державної політики у сфері забезпечення економічної безпеки держави: поняття та межі змісту - Кошиков, Д. О.; Koshykov , D. O. (Держава та регіони. Серія: Право. – 2020. – № 3 (69), т. 3. – С. 88-93, 2020)
Досліджено основні наукові підходи до розуміння адміністративного примусу. Опираючись на дослідження провідних вчених-адміністративістів, визначено перелік та розкрито зміст юридичних властивостей адміністративного примусу у розрізі його використання у якості методу реалізації державної політики у сфері забезпечення економічної безпеки держави. Наголошено на необхідності розмежування адміністративного примусу та контролю як методів реалізації державної політики у сфері забезпечення економічної безпеки держави.

It is noted that the sphere of competence of a fairly significant number of subjects of authority is inextricably linked to the implementation of state policy in the sphere of ensuring economic security, including through the implementation of administrative coercion, which is traditionally recognized as one of the universal methods of state administration. The main scientific approaches to the understanding of administrative coercion have been studied. Based on the research of leading administrative scientists, the list of legal properties of administrative coercion in terms of its use as a method of implementing state policy in the sphere of ensuring the economic security of the state is defined and revealed. The need to distinguish between administrative coercion and control as methods of implementing state policy in the sphere of ensuring the economic security of the state is emphasized. As a result, under administrative coercion as a method of implementation of state policy in the sphere of ensuring the economic security of the state, it is proposed to understand the application by authorized state bodies of executive power, in some cases by judges, to individuals and legal entities who are not under their command, regardless of the will and desire of the last measures of influence of a moral, property, organizational and personal nature in cases of committing or threatening to commit offenses by persons in the economic sphere, or in extraordinary circumstances with the aim of encouraging citizens to comply with universally binding rules, norms and standards in certain areas of economic management by preventing and stopping offences, punishment for their commission, as well as prevention and liquidation of the consequences of extraordinary circumstances with the help of simplified, operational administrative implementation. In turn, control is defined as a set of actions of subjects to monitor the functioning of the object of control with the aim of obtaining objective and reliable information about it; providing assistance to the controlled structure in restoring legality, established reasons and conditions contributing to the violation of the requirements of legal norms with the possibility of interfering in the operational activities of the controlled object by conducting inspections (audits). This definition is also characteristic of control as an administrative and legal method of implementing state policy in the sphere of ensuring the economic security of the state.

Исследованы основные научные подходы к пониманию административного принуждения. Опираясь на исследования ведущих ученых-административистов, определен перечень и раскрыто содержание юридических свойств административного принуждения в разрезе его использования в качестве способа реализации государственной политики в сфере обеспечения экономической сохранности страны. Отмечена необходимость разграничения административного принуждения и контроля как методов реализации государственной политики в сфере обеспечения экономической безопасности государства.
Administrative coercion as a method of implementation of state policy in the sphere of ensuring economic security of the state: concepts and content limits
Keywords: адміністративний примус; administrative coercion; административное принуждение; економічна безпека держави; economic security of the state; экономическая безопасность государства; державна політика; state policy; государственная политика